Identificación diferencial de objetivos y resultados de los planes de formación: una aplicación al sector de la acuicultura en España - Cruz González, María Monserrat; Sánchez Sellero, Francisco Javier (Pontificia Universidad Católica del Perú. Fondo Editorial, 2011)
The main aims of the formation, related theoretically to the performance of human resources, self-training, information and effectiveness, have been identified as the amount in which the company goes further from knowledge to learning. In this paper three hypotheses applied to the Spanish aquaculture are proposed to model the differential aim follow-up and the achievements of the formation plans. The empirical analysis has been carried out with the data of 99 representative companies of the aquaculture sector. The SPSS 19 statistical program was used for the data analysis. A factor analysis was made by the method of principal components. Eighteen nonparametric tests of Kruskal-Wallis type were applied, as well as 36 chi-squared tests. As a result, three principal components were identified that explain 80% of the variance of the aims: the first one refers to policies of implication of human resources, the second one is relatedto objective circumstances and the third one is associated to dynamism. It was confirmed that the relevance of aims is proportional to the percentage of expense in formation and, specifically, it is greater in suppliers. Finally, significantdifferences in the results of the formation with respect to the reduction of errors were observed, this reduction being greater in fish distribution and production. Significant differences were also observed in the effect of the formation on the motivation of the employee, this being greater in fish suppliers and producers

Los principales objetivos de la formación, relacionados teóricamente con el desempeño de los recursos humanos, el autoaprendizaje, la información y la eficacia, se han identificado como la medida en que la empresa transciende delconocimiento al aprendizaje. En este artículo se proponen tres hipótesis aplicadas al sector de la acuicultura en España para modelizar el seguimiento diferencial de objetivos y la consecución de resultados de los planes de formación. El análisisempírico se ha circunscrito a 99 empresas representativas del sector, cuya información ha sido tratada mediante el programa estadístico SPSS 19. Se llevó a cabo un análisis factorial por el método de componentes principales, 18 pruebas de Kruskal-Wallis y 36 pruebas no paramétricas chi-cuadrado. Como resultado, se identificaron tres componentes que explican un 80% de la varianza de objetivos: el primero referido a políticas de implicación de recursos humanos, el segundo relacionado con circunstancias objetivas y un tercero asociado al dinamismo. Se constató que la relevancia de objetivos es proporcional al porcentaje de gasto en formación y, específicamente, mayor en proveedores. Finalmente, se observaron diferencias significativas en los resultados de la formación respecto a la educción de errores, siendo mayores en distribución y producción de peces. También se observaron diferencias significativas en la motivación del empleado, mayor en proveedores y producción de peces.
Differential identification of aims and results of formation plans: an application to the Spanish aquaculture
Keywords: Formación; Acuicultura; Objetivos; Resultados; Aprendizaje; https://purl.org/pe-repo/ocde/ford#5.02.04